FtsH-Mediated Coordination of Lipopolysaccharide Biosynthesis in Escherichia coli Correlates with the Growth Rate and the Alarmone (p)ppGpp - Schäkermann, Michael (American Society for Microbiology, 2013)
The outer membrane is the first line of defense for Gram-negative bacteria and serves as a major barrier for antibiotics and other harmful substances. The biosynthesis of lipopolysaccharides (LPS), the essential component of the outer membrane, must be tightly controlled as both too much and too little LPS are toxic. In Escherichia coli, the cellular level of the key enzyme LpxC, which catalyzes the first committed step in LPS biosynthesis, is adjusted by proteolysis carried out by the essential and membrane-bound protease FtsH. Here, we demonstrate that LpxC is degraded in a growth rate-dependent manner with half-lives between 4 min and >2 h. According to the cellular demand for LPS biosynthesis, LpxC is degraded during slow growth but stabilized when cells grow rapidly. Disturbing the balance between LPS and phospholipid biosynthesis in favor of phospholipid production in an E. coli strain encoding a hyperactive FabZ protein abolishes growth rate dependency of LpxC proteolysis. Lack of the alternative sigma factor RpoS or inorganic polyphosphates, which are known to mediate growth rate-dependent gene regulation in E. coli, did not affect proteolysis of LpxC. In contrast, absence of RelA and SpoT, which synthesize the alarmone (p)ppGpp, deregulated LpxC degradation resulting in rapid proteolysis in fast-growing cells and stabilization during slow growth. Our data provide new insights into the essential control of LPS biosynthesis in E. coli.